Export Status and Productivity Performance: Evidence from Matched Italian Firms - Vito Amendolagine; Rosa Capolupo; Nadia Petragallo (Aussenwirtschaft, 2011)
This paper explores the two competing hypotheses of self-selection and learning by exporting across different Italian manufacturing firms.Using matched sampling techniques that control for selection bias,we estimate whether new export-oriented firms aremore efficient compared to domestic firms on the basis of three representative Surveys of Italian manufacturing firms covering consecutive triennial periods (from 1995 to 2003). By matching new exporting firms and non-exporters, our findings indicate that export entrants improve their productivity in the first period after entry although this effect vanishes in the subsequent period.This occurs for both total factor productivity (TFP) and labour productivity growth rates. Our evidence also suggests a positive causal effect of exporting on profitability since new exporters earn higher profits than their domestic counterparts do in every period after entry.
Keywords: F11; F14; O12; C22; 330; International trade; Export-led growth; Productivity; Matched techniques